MATHEMATICS TEACHERS’ ANXIETY IN TEACHING AND LEARNING PROCESS: A LITERATURE REVIEW - Freddy Prasetyo; Suhendra Suhendra; Turmudi Turmudi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Over the last few decades, many studies have placed attention on math anxiety in students, but math teachers can also experience anxiety that requires the attention. Math teachers can experience the anxiety in the form of math anxiety and math teaching anxiety, which can affect the learning process of mathematics. The purpose of this study is to identify the factors that cause math anxiety and math teaching anxiety in teachers. The method used in this research is Systematic Literature Review (SLR) with a survey-based descriptive approach through analysis the articles that fulfilled the inclution criteria, namely (1) published during the last ten years (2013-2022), (2) written in Indonesian or English, (3) indexed by Scopus or Sinta, which are browsed on the Google Scholar, ERIC, and Garuda database using the keywords “teachers’ math anxiety" and “teacher’s math teaching anxiety”. The results showed that mathematics teachers who experience mathematics anxiety in the form of feelings of worry and discomfort when thinking or doing something related to mathematics, this is caused by a low level of mathematics knowledge and self-confidence, while mathematics teaching anxiety causes worry and feeling uncomfortable when going to or teaching mathematics, this is caused by several factors such as experiencing mathematics anxiety, low mastery of learning technology, low levels of self-confidence, and unsupportive learning infrastructure.